What the New Measure of Thinking in School Students Has to Offer to Contemporary Education - Irina Uglanova; Irina Pogozhina (Voprosy obrazovaniya / Educational Studies Moscow, 2021)
For the pedagogical principle of assigning comprehensible and adequate tasks to be implemented, allowance should be made for students’ individual levels of logical reasoning, which requires diagnostic measures for objective and quick assessment. Today, the “clinical method” allows the most comprehensive assessment of logical thinking within the Piagetian framework. However, this diagnostic measure is extremely resource-consuming, hence unsuitable for large-scale testing. An overview of literature shows that the existing standardized diagnostic measures require a great number of highly-qualified experts to review the scores and prepare feedback for teachers, instructional designers, practicing psychologists and researchers. The article describes design methodology of an instrument to evaluate levels of logical reasoning that will allow automated scoring without sacrificing score meaning, eventually facilitating and accelerating the diagnostic measurement procedure. Implementation of these principles is analyzed using the example of computerized performance-based assessment of scenario-based problem solving in the form of stealth assessment of fifth- and seventh-grade pupils.